Japan's Militant Teachers A History of the Left-Wing Teachers' Movement - Duke, Benjamin C. (University of Hawai'i Press, 2018)
Educational developments in postwar Japan cannot be adequately understood today without a knowledge of the basic issues underlying the interminable controversy between the Japanese Ministry of Education and the left-wing Japan Teachers Union, Nikkyoso.Japan's Militant Teachers is the first comprehensive English-language analysis of the origin and development of the fundamental issues in this struggle. It is an objective approach to the history of the teachers' movement from its prewar conception, through the birth of Nikkyoso in 1947, to that union's present strength encompassing a large majority of all public school teachers. It is significant that this study was undertaken by a non Japanese. Professor Duke was accepted with full confidence by all parties in the dispute. His study includes material obtained from many firsthand interviews conducted between 1968 and 1970 with the leaders of Nikkyoso and government representatives from the Ministry of Education. He has thus been able to present an objective accounting without passing judgment.This book examines the problems of Nikkyosou within the greater context of Japanese society. It is a good introduction to, and analysis of, the problems facing organized teachers' movements as well as the problems facing Japanese education as a whole.